Impacts of organizational culture, support and IT infrastructure on knowledge management success: an imperial study in Islamic country, Saudi Arabia - Gharamah, Abdulrahman A.; Noordin, Mohamad Fauzan (The Institute of Electrical and Electronics Engineers, Inc., 2016)
Globalization and competitions are the main two challenges facing firms who are trying to sustain their success or even to stay in the market. Therefore, investments in technology, process and people become necessary for organizations to ensure having desired share in the marketplace. Large firms set up advanced and complex websites and hi-tech technology to create, maintain and share knowledge internally by accumulating and applying gained knowledge to create economic value. However, addressing organization culture and organization support and Information Technology (IT) infrastructure that impacting knowledge management is equally important. As those impacts have direct or indirect influence on people who are generating, utilizing and exchanging knowledge. The main objective of this research is to examine organization culture, organization support and Information Technology (IT) infrastructure factors that impact knowledge management in an organization. The major finding derived from the result is that, IT infrastructure predicts KMS. Meanwhile, the main Islamic implication derived from the finding is that, IT infrastructure should be value laden, by always observing the Islamic ethical principles in its operations.